Trust, family businesses and financial intermediation - Stacchini, Massimiliano; Degasperi, Petra (Journal of Corporate Finance, 2015)
This paper analyzes whether interpersonal trust affects the agency costs of family-controlled firms' debt. Our results are threefold. First, we find that banks apply a discount to the interest rates charged to family firms, whose size decreases considerably for contracts stipulated in high-trust areas. Second, as a response to the (unexpected) liquidity shock affecting the interbank market in August 2007, banks further increased the discount associated with family control. Third, we have no evidence of lender-corruption effects since the ex-post performance of the (cheaper) loans extended to the family firms is superior to that of their peers. These results suggest that banks deem the incentive structures prevailing in family firms to be able to attenuate the higher risks of expropriation run by lenders in areas where agency conflicts are greater, due to lack of interpersonal trust. Our findings are robust to the self-selection and omitted local variable problems as well as to credit demand-side effects. We model family control as an endogenous choice, introduce local-level fixed effects and use the heterogeneous exposure of Italian banks to the 2007–09 financial crisis – and the fact that Italian firms have more than one lender – to fully absorb changes in credit demand schedules.